2008
DOI: 10.1038/jcbfm.2008.114
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage Leads to Infiltration of Several Leukocyte Populations with Concomitant Pathophysiological Changes

Abstract: Intracerebral hemorrhage (ICH) is a stroke subtype with high rates of mortality and morbidity. The immune system, particularly complement and cytokine signaling, has been implicated in brain injury after ICH. However, the cellular immunology associated with ICH has been understudied. In this report, we use flow cytometry to quantitatively profile immune cell populations that infiltrate the brain 1 and 4 days post-ICH. At 1 day CD45 hi GR-1 + cells were increased 2.0-fold compared with saline controls (Pp0.05);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 28 publications
2
54
1
Order By: Relevance
“…6,25 Briefly, 3-4 hemorrhagic hemispheres were pooled for FACS analysis each time. Each hemisphere was digested in 1640 RPMI supplemented with 1 mg/mL collagenase IV (Sigma-Aldrich, C5138), 100 U/mL DNAse I (Sigma-Aldrich, D4263), 5 mM CaCl 2 , and 10% fetal bovine serum (FBS) for 40 min at 37…”
Section: Facs Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…6,25 Briefly, 3-4 hemorrhagic hemispheres were pooled for FACS analysis each time. Each hemisphere was digested in 1640 RPMI supplemented with 1 mg/mL collagenase IV (Sigma-Aldrich, C5138), 100 U/mL DNAse I (Sigma-Aldrich, D4263), 5 mM CaCl 2 , and 10% fetal bovine serum (FBS) for 40 min at 37…”
Section: Facs Analysismentioning
confidence: 99%
“…Meanwhile, the infiltration of inflammatory cells from the periphery further increases the inflammatory injury. [6][7][8] Inhibiting peripheral inflammatory cell infiltration using fingolimod can reduce inflammatory damage after ICH. 9,10 However, another study showed that fingolimod therapy is associated with increased neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…ICH is initiated by blood vessel rupture within brain parenchyma, resulting in mechanical and metabolic insults from the hematoma mass and blood components, respectively. These primary insults induce secondary inflammatory responses in the perihematomal region characterized by inflammatory cytokine production and leukocyte recruitment, which exacerbate brain damage (7)(8)(9). We have shown that inhibition of early inflammatory responses from MDMs ameliorates acute disability in murine ICH models (10,11), but the contribution of these cells to immune resolution and functional recovery has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…ICH initiates prominent inf lammatory responses, including the activation of resident glial cells and infiltration of circulating inflammatory cells into the brain (3,29,30). These inflammatory cells produce a number of proinflammatory mediators, such as TNF-α, IL-1β and IL-6 (31).…”
Section: Discussionmentioning
confidence: 99%